An Isotope Mass Balance Analysis of Evaporative Loss From Lake Turkana, Kenya Using δ18O and δD of Natural Waters - M. Saslaw; D. Yang; D. Lee; C. J. Poulsen; G. A. Henkes (Water Resources Research)
Abstract Measurements of oxygen and hydrogen stable isotope ratios (δ18O and δD) in meteoric waters provide insight to overlapping effects of evaporation, precipitation, and mixing on basin scale hydrology. This study of waters collected between 2016 and 2021 in the Turkana Basin, northern Kenya, uses δ18O and δD to understand water balance in Lake Turkana, a large, low‐latitude, alkaline desert lake. The Omo River, a major river system in the Ethiopian Highlands, is historically understood to provide approximately 90% of the water input to Lake Turkana. Discharge of the Omo is prohibitively difficult to measure, but stable isotope ratios in the lake may provide a meaningful method for monitoring the lake's response to changes in input. Precipitation in the Turkana Basin is low (<200 mm/year) with negligible rainfall on the lake's surface, and all water loss from the lake is evaporative. We compare new measurements with previous data from the region and records of lake height and precipitation from the same time period. We show that a Bayesian approach to modeling evaporation using atmospheric conditions and river δ18O and δD yields results consistent with published water balance models. Continued sampling of lake and meteoric waters in the Turkana Basin will be a useful way to monitor the lake's response to regional and global climate change.